2016
DOI: 10.1016/j.biomaterials.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic response of lung cancer cells to radiation in a paper-based 3D cell culture system

Abstract: (100-200 word limit)This work demonstrates the application of a 3D culture system, which is known as Cells-in-Gels-in-Paper or CiGiP, in evaluating the response of lung cancer cells to ionizing radiation. This system has four attributes: (i) multiple layers of paper, containing cell-embedded hydrogels, are assembled into a stack to form a thick (~800 µm) tissue-like construct, (ii) the metabolism of the cells, coupled with the boundary conditions imposed by an impermeable holder, generate a gradient of oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 78 publications
0
44
0
Order By: Relevance
“…Thus, 3D culture may be a powerful tool in tumor and relevant drug research. Marked advances have been made in the basic development of 3D tumor models so far, and prominent studies using 3D tumor cell models to simulate the tumor microenvironment or assess drug delivery in the past 5 years are summarized in Table I (6,8,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Considering the advantages of 3D tumor models, the present review provides an overview of the methods and techniques successfully devised for practicing 3D tumor cell culture.…”
Section: Current Preclinical Tumor Modelsmentioning
confidence: 99%
“…Thus, 3D culture may be a powerful tool in tumor and relevant drug research. Marked advances have been made in the basic development of 3D tumor models so far, and prominent studies using 3D tumor cell models to simulate the tumor microenvironment or assess drug delivery in the past 5 years are summarized in Table I (6,8,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Considering the advantages of 3D tumor models, the present review provides an overview of the methods and techniques successfully devised for practicing 3D tumor cell culture.…”
Section: Current Preclinical Tumor Modelsmentioning
confidence: 99%
“…As cells can migrate through the layer interface, they demonstrated chemotaxis of cancer following the oxygen concentration gradient . Furthermore, with a hypoxia‐inducible multilayer stack model, they demonstrated that an increased level of HIF‐1α was related to an increased radiation resistance ( Figure ) . In terms of the cancer–stromal cell interaction, Camci‐Unal et al demonstrated that the primary human lung tumor cells migrated toward the tumor fibroblasts by using multilayered paper scaffolds .…”
Section: Microphysiological Models Of Human Cancermentioning
confidence: 99%
“…[123][124][125][126][127] Paper has also been used for both fluidic compartments and cell scaffold. 128,129 Supernatants and perfusion media are then transferred to external readers or analysed in situ. Measurement is often limited to viability testing by optical methods such as fluorimetric live/ dead staining.…”
Section: Systems For 3d Cell Culture and Organ-on-chipmentioning
confidence: 99%